EFEKTIVITAS FORMULASI NANOPARTIKEL SENYAWA α ‑MANGOSTIN SEBAGAI TERAPI ADJUVAN PADA KARSINOMA HEPATOSELULER: TINJAUAN LITERATUR - Irfan, Akmal Jauhari; Anrofa, Farah Nabilah (ESSENTIAL: Essence of Scientific Medical Journal, 2026)
Introduction: Hepatocellular carcinoma (HCC) is a type of liver cancer with increasing incidence and mortality rates globally, including in Indonesia. Current HCC treatments, such as surgery, liver transplantation, radiotherapy, and targeted therapy, have limitations in terms of effectiveness, cost, and availability. α-Mangostin, a compound extracted from mangosteen, has been reported to exhibit anti-inflammatory, antioxidant, and anticancer activities. Therefore, this literature review aims to explore its potential as an innovative and effective adjuvant therapy for hepatocellular carcinoma. Discussion: α-Mangostin, a bioactive compound derived from mangosteen (Garcinia mangostana) fruit pericarp extract, has demonstrated anticancer activity through various mechanisms, including the induction of apoptosis, cell cycle arrest at the G0/G1 phase, and inhibition of tumor cell proliferation pathways. However, the limited bioavailability of α-mangostin hinders its therapeutic effectiveness. To overcome this, the formulation of α-mangostin with liposomal nanoparticles has been developed. Liposomes enhance the solubility, stability, and slow release of the active substance, allowing for increased effectiveness and reduced toxicity. Liposome-encapsulated α-mangostin has a lower IC50 than its free form and shows a more stable cytotoxic effect against HCC cells for a longer time. The combination of α-mangostin with conventional therapy, such as sorafenib, also showed synergistic effects in inhibiting tumor growth. Conclusion: α-Mangostin encapsulated in liposomal nanoparticles has excellent potential as an innovative adjuvant therapy in hepatocellular carcinoma. This formulation could become a more effective and economical alternative in the treatment of hepatocellular carcinoma.